Primary Appendiceal Lymphoma Presenting as Perforated Appendicitis: A Case Report - Sinha, Bipasha; Sutradhar, Arpita; Bhattacharya, Sandip Kumar; Goel, Vivek; Chakrapani, Anupam (Annals of Pathology and Laboratory Medicine, 2024)
Primary appendiceal lymphoma is very rare, representing about 0.015% of gastrointestinal lymphomas. It is difficult to diagnose clinically, as most cases present with symptoms resembling acute appendicitis. Here, we present a case of appendiceal lymphoma that presented with acute perforation, diagnosed through imaging as free air foci in the abdominal cavity. The patient was operated on, and the tissue was sent for histopathology, where a diagnosis of primary appendiceal lymphoma was made. A Fluoro-deoxyglucose Positron Emission Tomography (FDG-PET) scan was performed post-operatively, which showed extensive involvement of the abdominal cavity. Management is similar to that of primary gastrointestinal lymphoma, using a multimodal approach that includes surgery, chemotherapy, and radiotherapy. Due to her poor general condition, the patient could not tolerate the usual R-CHOP treatment, which includes cyclophosphamide, doxorubicin HCl, vincristine, and rituximab. Hence, she was started on mini-CHOP, which entails a reduced dosage of doxorubicin.